Debrett's kings and queens of Britain - Williamson, David (Topsfield, Mass. : Salem, 1986)
A survey of the monarchs of England, from the early Celtic and Saxon Kings to the House of Windsor. Additional notes and charts include the kings of Scotland, Wales, and Ireland.
Booklist.
Adult.
Adult
Keywords: Great Britain -- Kings and rulers -- Biography; Great Britain -- Queens -- Biography; Great Britain -- Kings, queens, rulers, etc. -- Biography